Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Sekolah Menengah Kejuruan Swasta “X” Pekanbaru - Yapentra, Arhipen (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
The research was conducted at Private Vocational High School (SMK) “X” Pekanbaru. The purpose of this study is to determine the impact of Principal Leadership on Teacher Performance at Private Vocational High School (SMK) “X” Pekanbaru. The research method is descriptive with quantitative approach, with the research population is teachers of Private Vocational High School (SMK)